2016
DOI: 10.1128/aem.01262-16
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Cobalt/Nickel Efflux OperondmeRFin Agrobacterium tumefaciens and a Link between the Iron-Sensing Regulator RirA and Cobalt/Nickel Resistance

Abstract: The Agrobacterium tumefaciens C58 genome harbors an operon containing the dmeR (Atu0890) and dmeF (Atu0891) genes, which encode a transcriptional regulatory protein belonging to the RcnR/CsoR family and a metal efflux protein belonging to the cation diffusion facilitator (CDF) family, respectively. The dmeRF operon is specifically induced by cobalt and nickel, with cobalt being the more potent inducer. Promoter-lacZ transcriptional fusion, an electrophoretic mobility shift assay, and DNase I footprinting assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…In our previous work, we found that the expression of two putative genes SM0020-17742 and SM0020-17737 was induced by Cu 2+ through transcriptome sequencing. The 966-bp-long open reading frame of SM0020-17742 encodes a 321-amino-acid protein, and the deduced protein shows high identity with several previously characterized cobalt- and nickel-resistant proteins: DmeF of C. metallidurans (ABF07084, 37%) and DmeF of A. fabrum (AAK86697, 52%), so we designated the SM0020-17742 gene dme F. In C. metallidurans and A. tumefaciens , the DmeF protein has an important role in cobalt and nickel resistance ( Dokpikul et al, 2016 ; Munkelt, Grass & Nies, 2004 ). However, the phylogenetic tree based on the DmeF protein sequence showed that the DmeF proteins of S. meliloti CCNWSX0020, S. arboris and S. medicae are more closely related to each other than that of C. metallidurans and A. tumefaciens ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, we found that the expression of two putative genes SM0020-17742 and SM0020-17737 was induced by Cu 2+ through transcriptome sequencing. The 966-bp-long open reading frame of SM0020-17742 encodes a 321-amino-acid protein, and the deduced protein shows high identity with several previously characterized cobalt- and nickel-resistant proteins: DmeF of C. metallidurans (ABF07084, 37%) and DmeF of A. fabrum (AAK86697, 52%), so we designated the SM0020-17742 gene dme F. In C. metallidurans and A. tumefaciens , the DmeF protein has an important role in cobalt and nickel resistance ( Dokpikul et al, 2016 ; Munkelt, Grass & Nies, 2004 ). However, the phylogenetic tree based on the DmeF protein sequence showed that the DmeF proteins of S. meliloti CCNWSX0020, S. arboris and S. medicae are more closely related to each other than that of C. metallidurans and A. tumefaciens ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, efflux systems, uptake systems, the synthesis of ligand compounds and metallochaperones for regulating cobalt and nickel homeostasis play a crucial role in most cobalt/nickel-resistant organisms. Among these cobalt/nickel-resistant systems, resistance nodulation cell division efflux pumps (RND) ( Stahler et al, 2006 ), cation diffusion facilitators (CDF) ( Dokpikul et al, 2016 ) and P 1b -type ATPases have been highlighted ( Rutherford, Cavet & Robinson, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…DmeR is a Ni(II)-and Co(II)-responsive metalloregulator that has been identified in Rhizobium leguminosarum (R. leguminosarum), Agrobacterium tumefaciens (A. tumefaciens), Sinorhizobium meliloti [81][82][83]. The dmeRF operon encodes both DmeR and DmeF, a cation diffusion facilitator (CDF) [81].…”
Section: Dmermentioning
confidence: 99%
“…DmeR has a RcnR-like finger print, HCHH ( Figure 6), and is therefore, expected to bind Ni(II) and Co(II) with six-coordinate octahedral geometry as seen in RcnR. It is interesting to note that cobalt stress induces the expression of iron-responsive genes in A. tumefaciens [82]. Additionally, RirA, an iron regulator, is essential for the bacteria to cope with nickel and cobalt toxicity [82].…”
Section: Dmermentioning
confidence: 99%
See 1 more Smart Citation